CREATING CHILD FRIENDLY ENGLISH CLASSROOM THROUGH THE ADOPTION OF LOCAL ENGLISH AS MEDIUM OF INSTRUCTION - Adityarini, Hepy (Jurnal Penelitian Humaniora, 2018)
The Child Right Convention articulated that education for children should be directed to respect their own cultural identity, language and values.Â  Similarly, from the perspectives of World Englishes the teaching of English is recommended to adopt local English as a way to empower the studentsâ local identity and accommodate their needs. This article is aimed at investigating the perspectives of English teachers working in primary education in Central Java Province, Indonesia. The data were gathered through interviews with 15 English teachers followed by questionnaires completed by 2033 English teachers. The results from the interviews showed that many teachers recognized the benefits of accommodating local English in the classroom for the children. Similarly, the majority of teachers completed the questionnaires positively predisposed of local English as the model for ELT in their local context.